The Conception and Historical Sources of Alternative Modern Schools - Valatkienė, Stasė (Acta Paedagogica Vilnensia, 2004)
The article presents the conception of alternative schools, emphasizes the need to establish alternative educational institutions. Also the tips of alternative schools are presented: independent, religious community, some private, humanistic schools - M. Montessori, Waldorf, experimental schools, alternative state schools - „magnet", charter and others (other classifications exist too). The main attention is paid to Montessori and Waldorf schools. The author discloses the historical development of alternative schools, discovers historical sources and the connections with new and progressive schools of the beginning of XX century in the Western Europe and USA.
Keywords: history of education; humanistic education; alternative schools; Waldorf school; Montessori